POTENTIAL INFLUENCE OF CULTURE MEDIUM CONSISTENCE AND SILVER NITRATE ON MICROPROPAGATION OF SOLANUM VIARUM, AN ANTICANCER MEDICINAL PLANT - 2Sujana Papani1* Naidu C.V (Journal of Biomedical and Pharmaceutical Research, 2017)
An understanding of optimal nutrient concentration could lead to increased growth and also could evoke maximum morphogenesis in vitro more effectively. Experiments were conducted to determine suitable combination of AgNO3 concentration and artificial nutrient media to stimulate in vitro growth of Solanum viarum. All the four types of basal media such as Murashige and Skoog (MS), Schenk and Hilderbrandt (SH), Gamberg media (B5) and K S medium were supplemented with 0 to 0.6 mg/L AgNO3, 2mg/L BAP, 0.5mg/L IAA, 3% sucrose and 0.8% of agar. Leaf explants supplemented with M S media responded the best at 0.4 mg/L AgNO3 with maximum mean shoot lengths (37.3 ± 0.46) and also with very high regeneration frequency (95%). Though maximum shoot lengths (10.2 ± 0.27 cm) were obtained in KS medium at 0.4mg/L AgNO3, the plantlets were found to be fragile and chloretic and were found to be very less feasible in the subsequent cultures. Explant had shown minimum response in SH medium and also nil response was recorded in case of B5 medium. So, MS media at 0.4 mg/L AgNO3 concentration was found to be more consistent media for conserving and propagating Solanum viarum under in vitro conditions. Key words: Solanum, Culture medium, Ethylene inhibitors, Shoot regeneration, Silver nitrate, Regeneration frequency